Understanding NK cell biology for harnessing NK cell therapies: targeting cancer and beyond - Shin, Eunju; Bak, Seong Ho; Park, Taeho; Kim, Jin Woo; Yoon, Suk-Ran; Jung, Haiyoung; Noh, Ji-Yoon (Frontiers in Immunology, 2023)
Gene-engineered immune cell therapies have partially transformed cancer treatment, as exemplified by the use of chimeric antigen receptor (CAR)-T cells in certain hematologic malignancies. However, there are several limitations that need to be addressed to target more cancer types. Natural killer (NK) cells are a type of innate immune cells that represent a unique biology in cancer immune surveillance. In particular, NK cells obtained from heathy donors can serve as a source for genetically engineered immune cell therapies. Therefore, NK-based therapies, including NK cells, CAR-NK cells, and antibodies that induce antibody-dependent cellular cytotoxicity of NK cells, have emerged. With recent advances in genetic engineering and cell biology techniques, NK cell-based therapies have become promising approaches for a wide range of cancers, viral infections, and senescence. This review provides a brief overview of NK cell characteristics and summarizes diseases that could benefit from NK-based therapies. In addition, we discuss recent preclinical and clinical investigations on the use of adoptive NK cell transfer and agents that can modulate NK cell activity.